Immunomodulating activity of lactic acid bacteria and bacillus microorganisms on experimental models - Shynkarenko, Sichel; Timoshok, Natalia; Lazarenko, Lyudmila; Starovoitova, Svitlana; Spivak, Mykola (My University, 2010)
One approach for the creation of highperformance probiotic preparations is a comparative study of their immunomodulating activity in experiments in vitro and in vivo.
Keywords: immunomodulating activity; lactic acid bacteria; Bacillus; імуномодулююча активність; молочнокислі бактерії; бацили; кафедра біотехнології і мікробіології